CHALLENGES OF INTEGRATING RESPONSIBLE MANAGEMENT EDUCATION IN HIGHER EDUCATION INSTITUTIONS OF UTTAR PRADESH, INDIA - Prakash, Ajai; Yadav, Archana (International Journal of Research -GRANTHAALAYAH, 2016)
India is facing a big debate on various social, economic and political issues which remained around corruption and poverty; how they can be eradicated from our society. Uttar Pradesh (U.P.) is the most populous state of our country with over 16.4 % of countries total population. Moreover with 9% of the country’s total geographical area, U.P. is the 4th largest state of our country. The median age of U.P. is 20 whereas that of India is young 24 years as in 2011. Though U.P. is the youngest state in India and has a rich cultural heritage but when it comes to literacy and gross enrolment in higher education, it is far behind other states. In order to create a responsible environment, management education can work as a very effective tool. In order to tackle the challenges faced globally such as corruption, poverty and workforce diversity, the United Nations has developed Responsible management initiative. The objective of this paper is to present the structure and different channels of management education in India with special reference to U.P. state. The focus is on identifying critical factors in integrating responsible management education in Higher Educational institutions with reference to sustainable development.